Fecal HBD-2 and Claudin-3 may be potential biomarkers to predict the deterioration of necrotizing enterocolitis: A prospective study - Liu, Xiao-Chen; Li, Lu-Quan; Ling, Ke-Ran; Guo, Lu; Hu, Xiao-Yu; Li, Chun (Frontiers in Pediatrics, 2022)
Abstract Background and purpose Necrotizing enterocolitis (NEC) is a critical gastrointestinal disease. We aim to explore the value of fecal Human β-defensin 2 (HBD-2), Claudin-3, high mobility group box-1 protein (HMGB-1) and resistin-like molecule β (Relmβ) as well as some laboratory metrics to predict the deterioration of NEC. Methods Infants diagnosed with NEC at stage II were enrolled in our study. Those progressed into stage Ⅲ were included in Stage Ⅲ Group and others were included in Stage II Group. Clinical data and laboratory metrics were collected. Fecal samples of HBD2, HMGB-1, Claudin-3 and Relmβ collected when enrolled were determined with enzyme-linked immunosorbent assay (ELISA) kits. Student’s t test, the Mann–Whitney U test, the chi-square test, Receiver operating characteristic (ROC) and logistic regression analysis were performed. Results Sixty infants diagnosed with NEC at stage Ⅱ were enrolled in our study with twenty-seven in Stage Ⅲ Group (n=27) and thirty-three in Stage Ⅱ Group (n=33). Though many of the cases of NEC enrolled in our study were late preterm and term infants, the infants had lower gestational age in Stage Ⅲ Group (P<0.05). The incidence of gestational diabetes mellitus, peritonitis, intestinal adhesion and sepsis were higher and more infants suffered surgeries in Stage Ⅲ Group (P<0.05). HBD-2 and Claudin-3 were higher and neutrophil count was lower in Stage Ⅲ Group than that in Stage Ⅱ Group and the AUC were 0.754, 0,755 and 0.666, respectively (P<0.05). HBD-2≥ 1649.02 ng/g and Claudin-3≥ 2488.71 pg/g were included in the multivariate stepwise logistic regression analysis (P<0.05), and the AUC of the model was 0.805 (95% CI: 0.688~0.922). Conclusion Fecal HBD-2 and Claudin-3 may be potential biomarkers to predict the deterioration of NEC from stage Ⅱ to Ⅲ.